Stratification and Chemistry Evolution of Ash Deposits During Combustion of Zhundong Lignite in a Drop Tube Furnace. (May 2017) - Li, Jianbo; Zhu, Mingming; Zhang, Zhezi; Zhang, Kai; Shen, Guoqing; Zhang, Dongke
Abstract: The structural stratification and chemistry evolution of the ash deposits formed on a probe during pf combustion of Zhundong lignite in a drop tube furnace operating at 1673 K was investigated. The ash deposits formed on the probe maintained at different temperatures for varying deposition times were then analysed using SEM-EDS. Results showed that the ash deposits formed in the first hour were composed of fine ash particles less than 25 μm and rich in Ca, Ca/S, and Fe, indicating that lime, anhydrite, and hematite were responsible for initiating the ash deposition. As deposition time increased, large irregular particles rich in Si, Al, and Na subsequently deposited on top of the layer of these fine ash particles. Moreover, the S/Ca ratio of the Ca-bearing ash particles increased as the deposit time on the probe increased, indicating that calcium sulphation reaction occurred on the probe. As the probe temperature increased from 823 K to 1023 K, the structure and chemistry of these deposits remained similar, however, the S/Ca ratio of the Ca-bearing ash particles increased, confirming that increasing the probe temperature promoted the sulphation reaction of calcium and helped sulphur capture.